Supramarginal gyrus involvement in visual word recognition. - Stoeckel, C; Gough, P; Watkins, K; Devlin, J (2009)
INTRODUCTION: In the classic neurological model of language, the human inferior parietal lobule (IPL) plays an important role in visual word recognition. The region is both functionally and structurally heterogeneous, however, suggesting that subregions of IPL may differentially contribute to reading. The two main sub-divisions are the supramarginal (SMG) and angular gyri, which have been hypothesized to contribute preferentially to phonological and semantic aspects of word processing, respectively. METHODS: Here we used single-pulse transcranial magnetic stimulation (TMS) to investigate the functional specificity and timing of SMG involvement in reading. Participants performed two reading tasks that focused attention on either the phonological or semantic relation between two simultaneously presented words. A third task focused attention on the visual relation between pairs of consonant letter strings to control for basic input and output characteristics of the paradigm using non-linguistic stimuli. TMS to SMG was delivered on every trial at 120, 180, 240 or 300 msec post-stimulus onset. RESULTS: Stimulation at 180 msec produced a reliable facilitation of reaction times for both the phonological and semantic tasks, but not for the control visual task. CONCLUSION: These findings demonstrate that SMG contributes to reading regardless of the specific task demands, and suggests this may be due to automatically computing the sound of a word even when the task does not explicitly require it.